PENERAPAN PENGENDALIAN PERSEDIAAN MENGGUNAKAN METODE SAFETY STOCK DAN REORDER POINT UNTUK MENINGKATKAN EFISIENSI BIAYA PERSEDIAAN PEMPEK - Nugraha, Arie Apriadi; Pahirva, Rama; Firdaus, Muhammad Hafizh (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2024)
Inventory control is crucial as many businesses invest significantly in their inventory. Excessive investment leads to high storage costs, while insufficient inventory results in additional costs and stockouts. Pempek RATU’s sales and profits declined by nearly 50% in 2023 due to poor inventory control and high inventory costs. This research aims to increase the efficiency of Pempek inventory costs by applying safety stock and reorder point methods. It employs a descriptive quantitative approach, focusing on Pempek supplies. The company's current safety stock calculation is based on observing sales over the past three months without considering the quantity of goods ordered. whereas, the company's reorder point calculation only considers the remaining stock, neglecting total forecast, safety stock, and delivery time. Meanwhile, in this study, researchers abserve to these things.